2015
DOI: 10.11604/pamj.2015.22.152.6677
|View full text |Cite
|
Sign up to set email alerts
|

Prévalence de l’hypertension artérielle dans la population des meuniers de la ville de Lubumbashi, République Démocratique du Congo

Abstract: IntroductionL'objectif était de comparer la prévalence de l'hypertension artérielle chez les meuniers dans la ville de Lubumbashi qui sont exposés d'une manière permanente aux bruits des machines de transformation des céréales à la prévalence de l'hypertension artérielle chez un groupe des gardiens.MéthodesQuic'est une étude descriptive transversale qui a concerné 286 meuniers et 115 agents d'une entreprise de gardiennage. Apres un consentement éclairé, un auto questionnaire a été administré aux enquêtés et de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
1
6
1
6
Order By: Relevance
“…For a better understanding of the burden of hypertension, Jingi et al [4] suggested that epidemiological studies on hypertension should be reported according to the professional category. Compared to other professional categories, the prevalence of hypertension in this study was significantly lower than the 49.3% and 20.9% reported by Ngombe et al [9] in a group Millers and Security workers respectively in the Democratic Republic of Congo. Koffi et al [10] reported a significantly higher rate of hypertension (29.7%) in a group of seaport workers in Ivory Coast, and Fouda et al [11] reported a significantly higher rate of hypertension (24.8%) in a group of workers from six enterprises in Douala-Cameroon.…”
Section: Discussioncontrasting
confidence: 82%
“…For a better understanding of the burden of hypertension, Jingi et al [4] suggested that epidemiological studies on hypertension should be reported according to the professional category. Compared to other professional categories, the prevalence of hypertension in this study was significantly lower than the 49.3% and 20.9% reported by Ngombe et al [9] in a group Millers and Security workers respectively in the Democratic Republic of Congo. Koffi et al [10] reported a significantly higher rate of hypertension (29.7%) in a group of seaport workers in Ivory Coast, and Fouda et al [11] reported a significantly higher rate of hypertension (24.8%) in a group of workers from six enterprises in Douala-Cameroon.…”
Section: Discussioncontrasting
confidence: 82%
“…Une relation entre l'HTA et le travail a été établie par plusieurs études à l'échelle mondiale [4][5][6][13][14][15][16][17][18]. Les prévalences d'HTA restent cependant variables chez les travailleurs tant dans les pays en développement que dans les pays développés [4][5][6][13][14][15][16][17][18]20,21].…”
Section: De Facteurs Sociodémographiquesunclassified
“…En Afrique, la prévalence de l'HTA en milieu professionnel varie d'un pays à un autre et selon l'activité professionnelle, ce qui a été rapporté dans plusieurs séries africaines [3,8,13,[16][17][18]20]. En milieu professionnel, cette prévalence de l'HTA dépend à la fois de la profession et des conditions de travail.…”
Section: De Facteurs Sociodémographiquesunclassified
See 2 more Smart Citations